2020
DOI: 10.1002/anie.201912412
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide Is Not a Promoter of C2+ Product Formation in the Electrochemical Reduction of CO on Copper

Abstract: Highly alkaline electrolytes have been shown to improve the formation rate of C2+ products in the electrochemical reduction of carbon dioxide (CO2) and carbon monoxide (CO) on copper surfaces, with the assumption that higher OH− concentrations promote the C−C coupling chemistry. Herein, by systematically varying the concentration of Na+ and OH− at the same absolute electrode potential, we demonstrate that higher concentrations of cations (Na+), rather than OH−, exert the main promotional effect on the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 53 publications
4
79
0
1
Order By: Relevance
“…These results are in contrast with a previous report using Cu foils, on which clear mass transport limitation of CO was observed at more negative potentials 32 , 47 . The physical characterizations of Cu MPs were previously reported by our group 42 . All C 2+ products exhibit a similar Tafel slope of ~118 mV dec −1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in contrast with a previous report using Cu foils, on which clear mass transport limitation of CO was observed at more negative potentials 32 , 47 . The physical characterizations of Cu MPs were previously reported by our group 42 . All C 2+ products exhibit a similar Tafel slope of ~118 mV dec −1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the local [OH – ], which increases with increasing CO (2) R current, plays no direct role in promoting the rate of these two steps 23 , since they are driven by the field alone . However, the [OH – ] can alter the CO 2 concentration through the bicarbonate equilibria, suppress CH 4 formation 14 , and promote the activity towards acetate, even at a fixed U vs. SHE 24 .…”
Section: The Activity Towards Co and C 2 Products mentioning
confidence: 99%
“…[25,26,40] We performed a control experiment where we progressively incorporated 18-crown-6 ether to a 0.5 M KHCO 3 solution to selectively chelate K + (denoted crown-K + , see illustration on Figure S8a, b). [41,42] The purpose of this experiment was to modulate the charge density at the OHP (by changing the effective cation size compared to solvated K + ), while preventing the polarization of water molecules contained in the hydration shell of the cation. We found that the FE CO values decreased by~15 % as the [18crown-6 ether] was increased from 0 M to 0.5 M (K + is chelated by equimolar amounts of 18-crown-6 ether) during electrolysis at a constant applied current density of 100 mA cm À 2 (Figure S8c).…”
Section: Effect Of Cation Identity On Bicarbonate Electrolysis and Co2rr Catalyst Activitymentioning
confidence: 99%